2011
DOI: 10.1002/ijc.25546
|View full text |Cite
|
Sign up to set email alerts
|

Gamma‐tocotrienol as an effective agent in targeting prostate cancer stem cell‐like population

Abstract: Emerging evidence supports that prostate cancer originates from a rare subpopulation of cells, namely prostate cancer stem cells (CSCs). Conventional therapies for prostate cancer are believed to mainly target the majority of differentiated tumor cells but spare CSCs, which may account for the subsequent disease relapse after treatment. Therefore, successful elimination of CSCs may be an effective strategy to achieve complete remission from this disease. Gamma‐tocotrienols (γ‐T3) is one of the vitamin‐E consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 49 publications
3
68
1
Order By: Relevance
“…43 Gamma-tocotrienols (gamma-T3), one of the vitamin-E constituents, can inhibit the tumorigenicity of prostate cancer cells and kill docetaxel-resistant CD133-enriched PC-3 prostate cancer cells. 44 Parthenolide, a sesquiterpene lactone well known in natural medicine, can reverse the vinorelbine resistance of SP cells in MCF-7 breast cancer cells. 45 A combination of stealthy liposomal vinorelbine and stealthy liposomal parthenolide can fully inhibit the MCF-7 cell xenograft growth.…”
Section: Salinomycinmentioning
confidence: 99%
“…43 Gamma-tocotrienols (gamma-T3), one of the vitamin-E constituents, can inhibit the tumorigenicity of prostate cancer cells and kill docetaxel-resistant CD133-enriched PC-3 prostate cancer cells. 44 Parthenolide, a sesquiterpene lactone well known in natural medicine, can reverse the vinorelbine resistance of SP cells in MCF-7 breast cancer cells. 45 A combination of stealthy liposomal vinorelbine and stealthy liposomal parthenolide can fully inhibit the MCF-7 cell xenograft growth.…”
Section: Salinomycinmentioning
confidence: 99%
“…Cardioprotective effects of tocotrienols were mediated through inhibition of HMG-CoA reductase, a rate limiting enzyme in cholesterol biosynthesis [13]. There are several reports on antitumor activity of GT on human mammary tumor cells [11], hepatocellular carcinoma [14], colon cancer cells [15], melanoma cells [16,17], gastric adenocarcinoma [18][19][20] and prostate cancer cells [10]. GT has been shown to suppress multiple signaling pathways that include suppression of NF-B, STAT3, cell cycle regulatory proteins (Rb/E2F complex, cyclin D1/cdk4 and cyclin B1/cdk1) and phosphatidylinositol 3-kinase (PI3K)-AKT signaling [21][22][23].…”
Section: Introductionmentioning
confidence: 97%
“…This higher cellular uptake has been attributed to their superior biological activities as compared to tocopherols [6]. Hence, tocotrienols are known as super vitamin E. Among these isoforms, -tocotrienol (GT) has been shown to display potent antioxidant [7][8][9] and anticancer activities [10,11]. Tocotrienols have been shown to suppress the expression of TNF, IL-1, IL-6, IL-8, inducible nitric oxide synthase, and cyclo-oxygenase 2, all of which mediate inflammation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have also established that γ-and δ-tocotrienols, and to a lesser extent α-tocotrienol, were able to induce apoptosis in breast cancer, hepatocellular, and melanoma cells (5). Similarly, tocotrienols proved their effective anticancer activity against prostate cancer where in their study, Luk and colleagues demonstrated γ-tocotrienol to prevent chemoresistance by eliminating prostate cancer stem cells in androgen-independent pathway (36). Furthermore, recent in vitro studies in the highly malignant+SA mammary tumor cell line demonstrated an inhibitory effect of γ-tocotrienol on Met expression and activation where γ-tocotrienol significantly inhibited the HGF-dependent+SA cell replication (37), an effect that was further enhanced by its combined treatment with SU11274, a Met inhibitor, in various mammary cancer cell lines (38).…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 96%